Expectant management of severe preeclampsia in mid-trimester: a hospital based study - Pandey, Uma; Thapa, Shreya; Singh, Jigyasa; Sharan, Jyotsana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to determine the maternal and perinatal outcome of the expectant management of severe preeclampsia between 24 weeks and 34 weeks of gestation. Methods: Data was collected from the 50 case notes of the mothers who had expectant management of severe preeclampsia. The study period was April 2011-March 2013. Total of 27 women in the year 2011-2012 (April-March) and 23 women in the year 2012-2013 (April-March) were included. Maternal condition was carefully monitored with the help of non-invasive monitors. Fetal condition was monitored by ultrasound and colour Doppler. Number of days as pregnancy prolongation and maternal and perinatal morbidities were calculated and analysed. Results: The number of days prolonged has been maximum in gestational age of 28-30 weeks, median being 23.5. There is association between higher maternal DBP and appearance of maternal complications (as DBP increases mother is more at risk). Conclusions: Pregnancies complicated by severe preeclampsia can be managed expectantly in a tertiary care centre of India (low resource country) provided mother and fetus are monitored for their wellbeing.